(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The present study was conducted at the Biotechnology Laboratory, Biotechnology Division, Bangladesh Agricultural Research Institute (BARI), Gazipur during the period from September 2004 to June 2005 to investigate the effect of different concentrations of BAP and NAA on virus free plant regeneration, shoot multiplication and different concentrations of IBA and IAA on in vitro root formation of banana cv. BARI Banana-I. The culture meristem first turned brown in colour in 4-5 days which grew into a green globular hard coat mass after 30-35 days. From this ball like structure, adventitious plantlets were developed. Among the different concentrations, 7.5 mg/l BAP + 0.5 mg/l NAA showed highest shoot proliferation of 0.75, 2.75 and 6.25 shoots per explant at 10, 20 and 30 DAI, respectively. The longest shoot (1.03, 2.45 and 3.38 cm) at 10, 20 and 30 DAI, respectively, was produced by the treatment combination of 7.5 mg/l BAP + 0.5 mg/l NAA. The maximum number of leaves (2.50, 3.25 and 7.00 leaves/explant at 10, 20 and 30 DAI) were produced on the medium supplemented with the same treatment and it also produced the longest leaves, 0.85, 2.70 and 4.23 cm at 10, 20 and 30 DAI, respectively. For root initiation half strength MS medium supplemented with different levels of IBA (0, 0.5, 1 .0 and 1.50 mg/l) and IAA (0, 0.5 and 1.0 mg/l) was used. Root numbers varied with different concentrations of IBA and IAA. The highest number of roots were produced by 0.5 mg/l IAA + 0.5 mg/l IBA. The highest length (2.93, 4.63 and 5.88 cm) was recorded at 10, 20 and 30 DAI in the same treatment which was statistically significant. Meristem derived plantlets were transferred to poly bags containing 1:1 (ground soil : cowdung) mixture after 7 days hardening in room temperature (28-30°C) and established plantlet was ready for planting. Key Words: Banana; regeneration; micropropagation; plantlet. DOI: 10.3329/bjar.v34i4.5840 Bangladesh J. Agril. Res. 34(4) : 645-659, December 2009